AN ELEMENT OF PRACTICAL KNOWLEDGE IN EDUCATION: PROFESSIONAL ROUTINES - Lacourse, France (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2011)
ABSTRACT. The question of practical knowledge and its teaching has arisen more perceptibly since the appearance of the aim to professionalize teachers. How can imperceptible knowledge such as professional routines be taught? To establish a social fabric and effective class management, it is essential to call on creative and adaptive professional routines. These routines support the interpretation of daily life, effectiveness, and a sense of security among both students and teachers; it is a frame favouring successful classroom management. Professional routines come under the scope of integrated competencies, and this prompts their analysis in view of understanding a central link within initial training. This paper will present the concept of professional routines as an educational practice in which practical knowledge is combined with professional learning, then the conceptual frame, the analytical method, and the results of two research projects, followed by a concluding reflection. ÉLÉMENT D’ANALYSE DU SAVOIR PRATIQUE EN ENSEIGNEMENT: LES ROUTINES PROFESSIONNELLES RÉSUMÉ. La question du savoir pratique et de son enseignement se pose de manière plus perceptible depuis la visée de professionnalisation de l’enseignant. Comment enseigner un savoir imperceptible comme des routines professionnelles? Pour construire un tissu social et une gestion de classe efficace, il est essentiel de recourir à des routines professionnelles adaptatives et créatives. Les routines à l’œuvre soutiennent alors l’interprétation du quotidien, l’efficacité et le sentiment de sécurité tant chez l’enseignant que chez les élèves, c’est un cadre qui favorise la réussite en gestion de classe. Les routines professionnelles relèvent de compétences incorporées, ce qui force à leur analyse pour une articulation phare opérant en formation initiale et continue. Nous présenterons le concept des routines professionnelles comme une pratique éducative où savoir pratique et apprentissage professionnel se conjuguent, le cadre conceptuel, une méthode d’analyse, les résultats de deux recherches, pour conclure sur une réflexion.